ANALISIS MAKNA KONOTATIF DALAM KUMPULAN PUISI KISAHKU KARYA MIEKE NURHAYATI - Fatou'osa Laia (Universitas Nias Raya, 2026)
This research was motivated by the researcher's desire to identify the connotative meaning in the poetry collection